Kewenangan Mahkamah Konstitusi Dalam Memutus Perselisihan Hasil Pemilu Sebagai Bentuk Judicialization of Politic - Ida Bagus Putu Sudiartha; Erikson Sihotang; I Nyoman Suandika (Ethics and Law Journal: Business and Notary, 2024)
This research aims to train students in writing scientific papers, implement the Tri Dharma of Higher Education, especially in the field of research, obtain a bachelor's degree in law, and develop students' personalities in social life. In addition, this research also aims to find out the authority of the Constitutional Court (MK) in making decisions related to disputes over election results as a form of Judicialization of Politics, and to find out the impact of MK decisions in disputes over election results on political polarization in society. The Constitutional Court (MK) was established to resolve political and constitutional cases, including disputes over election results, in accordance with constitutional principles. The authority of the Constitutional Court as a form of judicialization of politics must be balanced with judicial restraint so as not to become the object of politicization. Restrictions on the interpretation of structured, systematic and massive (TSM) are needed to prevent politicization and reduce the authority of other institutions such as Bawaslu. The 1945 Constitution grants four authorities and one constitutional obligation to the Constitutional Court, which requires procedural law to regulate procedural mechanisms. This procedural law serves to enforce material law, develop new law, and uphold the law in Indonesia. Keywords: Constitutional Court, Election Results Dispute, Judicialization of Politics, Judicial Restraint Abstrak Penelitian ini bertujuan untuk melatih mahasiswa dalam penulisan karya ilmiah, melaksanakan Tri Dharma Perguruan Tinggi khususnya di bidang penelitian, memperoleh gelar sarjana dalam bidang ilmu hukum, dan mengembangkan pribadi mahasiswa dalam kehidupan bermasyarakat. Selain itu, penelitian ini juga bertujuan untuk mengetahui kewenangan Mahkamah Konstitusi (MK) dalam pengambilan keputusan terkait perselisihan hasil pemilu sebagai bentuk Judicialization of Politics, serta mengetahui dampak keputusan MK dalam perselisihan hasil pemilu terhadap polarisasi politik di masyarakat. Mahkamah Konstitusi (MK) didirikan untuk menyelesaikan perkara politik dan ketatanegaraan, termasuk perselisihan hasil pemilu, sesuai prinsip konstitusi. Kewenangan MK sebagai bentuk judicialization of politics harus diimbangi dengan pembatasan diri (judicial restraint) agar tidak menjadi objek politisasi. Pembatasan tafsiran terstruktur, sistematis, dan masif (TSM) diperlukan untuk mencegah politisasi dan mengurangi kewenangan lembaga lain seperti Bawaslu. UUD 1945 memberikan empat kewenangan dan satu kewajiban konstitusional kepada MK, yang memerlukan hukum acara untuk mengatur mekanisme beracara. Hukum acara ini berfungsi menegakkan hukum materiil, mengembangkan hukum baru, dan menegakkan hukum di Indonesia. Kata Kunci: Mahkamah Konstitusi, Perselisihan Hasil Pemilu, Judicialization of Politics, Judicial Restraint